Quality Appraisal of Child Oral Health–Related Quality of Life Measures: A Scoping Review. (April 2020) - Yang, C.; Crystal, Y.O.; Ruff, R.R.; Veitz-Keenan, A.; McGowan, R.C.; Niederman, R.
Background: Children's oral health–related quality of life (COHQoL) measures are well known and widely used. However, rigorous systematic reviews of these measures and analyses of their quality are in absence. Objectives: To systematically review and quantitatively assess the quality of COHQoL measures through a scoping review. Data Sources: Systematic literature search of PubMed, CINAHL (Cumulative Index to Nursing and Allied Health Literature), EMBASE (Excerpta Medica database), HaPI (Health and Psychosocial Instruments), and DOSS (Dentistry and Oral Sciences Source). Study Eligibility: The measure's focus was COHQoL; the child age ranged from 5 to 14 years; the publication was either a research article or a systematic review and related to caries; and it was written in English or had an English abstract. Two authors independently selected the studies. Disagreements were reconciled by group discussions with a third author. Appraisal: The International Society for Quality of Life Research minimum standards for patient-reported outcome measures were used for quality appraisal. Synthesis: Descriptive analysis. Results: We identified 18 measures. Their quality scores ranged from 9.5 to 15.0 on a scale of 16. The quality appeared to bear no relationship to the citation and use of these measures. However, elements of these measures might be more useful than others, depending on the age-specific use and primary quality concerns. Limitations: Some of the information on the minimum standards of the 18 measures cannot be found in the existing literature. Measures published without English abstract were not searched. Conclusions: The quality of these measures is suboptimal. Researchers and practitioners in this field should exercise caution when choosing and using these measures. Efforts at improving the quality of the COHQoL measures, such as refining existing ones or developing new measures, are warranted. Knowledge Transfer Statement: Researchers, clinician scientists, and clinicians can use the results of this study when deciding which oral health–related quality of life measure they wish to use in children.